The Effect of Toddler Nutrition Patterns on Toddler Growth (1-5 years) in Tandem Hilir I Village, Deli Serdang Regency - Maimunah R; Yuni Ramadhani; Pebrinawati Pebrinawati; Julidia Safitri Parinduri (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
The toddler period is a critical period or “golden age” that determines the quality of future growth and development. Globally, stunting remains a major challenge, with an estimated 150.2 million children affected in 2024. In Indonesia, the prevalence of stunting reached 21.5% according to the 2023 Indonesian Health Survey (SKI). Optimal nutrition through proper diet is a key determinant in preventing linear growth failure and maintaining toddler health. This study aims to analyze the relationship between toddler nutritional intake patterns and growth trends among toddlers aged 1-5 years in Tandem Hilir I Village, Deli Serdang District. This study used a quantitative analytical observational design with a cross-sectional approach. The study was conducted in April 2025 in the working area of the Tandem Hilir I Village Health Center. The study sample consisted of 58 mothers of toddlers selected using the total sampling (saturated sample) technique. The independent variable (eating habits) was measured using a structured questionnaire adapted from the Balanced Nutrition Guidelines with a Cronbach's alpha value of 0.82. The dependent variable (growth) was assessed through longitudinal data in the Health Card (KMS) or Maternal and Child Health Book (Buku KIA) for the last three months. The data were statistically analyzed using the chi-square (X2) test with a significance level of alpha = 0.05. Bivariate analysis revealed that 71.42% of toddlers with good eating patterns experienced optimal growth, while 34.78% of toddlers with poor eating patterns tended to experience stunting or weight loss. The chi-square test results showed a calculated X2 value of 7.5, which was greater than the X2 table value of 2.841 (p < 0.05), indicating a statistically significant relationship between nutritional intake patterns and toddler growth. There is a clear correlation between the quality of eating habits and the physical growth trajectory of children in the study location. Growth failure is more influenced by low nutritional literacy and the transition to low-nutrient processed foods Keywords: Toddler Diet, Growth, Stunting, Deli Serdang, Balanced Nutrition